High-durability environment-friendly steel slag concrete and preparation method thereof

By adding carboxylic glycoside derivatives with carboxylate to the steel slag powder and soaking the sulfate, the problem of insufficient durability of steel slag concrete is solved, and steel slag concrete with high durability and environmental protection is achieved.

CN119841590APending Publication Date: 2025-04-18TAIZHOU EAST BUILDING MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510159315.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing steel slag concrete has insufficient durability, resulting in limited application range.

Method used

By adding carboxylic glycoside derivatives to the steel slag powder and soaking the steel slag particles in soluble inorganic sulfates, the alkali content and dissolution of heavy metal ions are reduced, and the stability of the steel slag powder is improved.

Benefits of technology

It significantly improves the durability and environmental protection of steel slag concrete, enhances its protection against moisture and harmful media, and extends the service life of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005270543050000061
    Figure BDA0005270543050000061
  • Figure BDA0005270543050000071
    Figure BDA0005270543050000071
Patent Text Reader

Abstract

The invention discloses high-durability environment-friendly steel slag concrete and a preparation method thereof. The high-durability environment-friendly steel slag concrete is prepared from the following raw materials in parts by mass: 70 to 86 parts of steel slag powder, 300 to 320 parts of cement, 287 to 296 parts of aggregate, 112 to 120 parts of sand, 1.3 to 2.2 parts of water reducing agent and 2.4 to 3.1 parts of glucoside derivative with carboxyl. The glycoside derivative with carboxyl can react with redundant alkali substances to inhibit alkali aggregate reaction in the concrete curing process, negative ions obtained after reaction contain carboxylate radicals and a plurality of hydroxyl groups, can chelate heavy metal ions and further can destroy double-electrode-layer structures on the surfaces of steel slag powder particles and cement particles in mixed concrete, and the concrete curing effect is improved. The fluidity of the concrete is improved, the bonding mode of steel slag powder particles and cement particles is changed, microcracks and pores in the concrete are reduced, concrete particles are bonded more tightly, and the strength and durability of the environment-friendly steel slag concrete are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to building materials, and in particular to a highly durable environmentally friendly steel slag concrete and a preparation method thereof. Background Art

[0002] Steel slag is a byproduct of the steelmaking process, and its emission is about 10-15% of steel production. The stacking and idleness of a large amount of steel slag not only occupies a large amount of arable land, but also the heavy metal ions and alkali metal ions contained in the steel slag will penetrate into the soil, causing groundwater pollution. At the same time, steel slag contains C3S, C2S and other water-hardening components, so steel slag has a certain activity.

[0003] At present, there are steel slag concretes that use steel slag to replace part of the gel material. In practical applications, the impact of the stability of steel slag on the durability of concrete needs to be considered. Steel slag contains a high amount of alkali. When the water-binder ratio remains unchanged, increasing the amount of steel slag added will not only reduce the strength of steel slag concrete, but also cause more cracks in the concrete components due to the insufficient performance of steel slag as a gel material and the enhancement of alkali-aggregate reaction. Increasing the permeability of concrete means that the interior of the concrete is more susceptible to the invasion of harmful substances such as moisture and chloride ions, thereby reducing the durability of steel slag concrete.

[0004] Therefore, solving the durability problem of steel slag concrete is the key issue to expand the application scope of steel slag concrete. Summary of the invention

[0005] In order to expand the application scope of steel slag concrete, a highly durable and environmentally friendly steel slag concrete and a preparation method thereof are provided.

[0006] The above first invention objective of the present invention is achieved through the following technical solutions: A highly durable environmentally friendly steel slag concrete comprises the following raw materials in parts by weight: 70-86 parts of steel slag powder, 300-320 parts of cement, Aggregate 287-296 parts, 112-120 parts of sand, 1.3-2.2 parts of water reducing agent, 2.4 to 3.1 parts of glycoside derivatives with carboxyl groups.

[0007] By adopting the above technical scheme, the glycoside derivatives with carboxyl groups can react with excess alkaline substances to inhibit the alkali-aggregate reaction during the concrete curing process; the anions obtained after the reaction of the glycoside derivatives with carboxyl groups have carboxylate groups and multiple hydroxyl groups, which can chelate heavy metal ions on the one hand, and on the other hand can also destroy the double electric layer structure on the surface of steel slag powder particles and cement particles in the mixed concrete, improve the fluidity of the concrete, change the bonding mode of steel slag powder particles and cement particles, reduce microcracks and pores inside the concrete, and make the concrete particles more tightly bonded, prevent moisture and other harmful media from penetrating into the concrete, thereby improving the strength and durability of the concrete, thereby obtaining a highly durable environmentally friendly steel slag concrete.

[0008] Optional: The glycoside derivative with a carboxyl group is glucuronic acid.

[0009] By adopting the above technical solution, the effect of using glucuronic acid in the present application is better.

[0010] Optionally, the steel slag powder is a modified steel slag powder, which is obtained by grinding steel slag particles after soaking them in a soluble inorganic sulfate.

[0011] By adopting the above technical scheme, the steel slag particles are immersed in a soluble inorganic sulfate, and part of the alkaline substances in the steel slag are dissolved, thereby reducing the alkali content in the steel slag powder. On the other hand, during the immersion treatment, part of the heavy metals in the steel slag are also dissolved and converted into insoluble or insoluble precipitates, reducing the amount of soluble heavy metals in the steel slag powder. In addition, the formed precipitates will compensate for the loss of substances in the steel slag after dissolution, thereby improving the stability of the steel slag powder, thereby improving the durability and environmental friendliness of the environmentally friendly steel slag concrete.

[0012] Optionally: the soluble inorganic sulfate is a compound of sodium sulfate and aluminum sulfate.

[0013] By adopting the above technical scheme, due to the difficulty of ion diffusion during the immersion treatment of steel slag particles, the concentration of alkaline substances in the micropores of the steel slag particles is the highest, the surface is second, and the concentration of the surrounding solution is the lowest. In order to ensure the high recoverability of the steel slag particles and reduce the loss of steel slag during the immersion treatment process, stirring is generally not performed during the immersion process. Sodium sulfate and aluminum sulfate are compounded, and the aluminum ions dissolved in aluminum sulfate are dispersed in the aqueous phase and penetrate into the micropores of the steel slag. The reaction with hydroxide accelerates the dissolution of alkaline substances in the steel slag, and can improve the stability of the steel slag powder, thereby improving the durability and environmental protection of the environmentally friendly steel slag concrete.

[0014] Optionally, the molar ratio of the sodium sulfate to the aluminum sulfate is 100:4-10.

[0015] By adopting the above technical solution, the obtained environmentally friendly steel slag concrete has excellent durability, strength and environmental protection.

[0016] Optional: also includes 1.3 to 1.9 parts of magnesium phosphate.

[0017] Through the above technical solution, the early strength of concrete can be improved, heavy metal ions can be solidified, the microstructure and density of concrete can be improved, thereby improving its overall durability. In addition, magnesium phosphate cement also has good resistance to sulfate erosion, which helps to extend the service life of concrete.

[0018] Optional: The water reducing agent is magnesium lignin sulfonate.

[0019] By adopting the above technical solution, in addition to the effect of the water reducer, the heavy metal ions can be further solidified, thereby reducing the possibility of heavy metal ions migrating from concrete to the environment in the long term, and improving the environmental protection of steel slag concrete.

[0020] The above second invention objective of the present invention is achieved through the following technical solutions: A method for preparing highly durable environmentally friendly steel slag concrete comprises the following steps: Mix water, water reducing agent and glycoside derivative with carboxyl group to obtain preparation water. The remaining raw materials such as steel slag powder, cement, aggregate, sand and the preparation water are evenly mixed to obtain highly durable environmentally friendly steel slag concrete.

[0021] By adopting the above technical scheme, the water reducing agent and the glycoside derivative with a carboxyl group are fully and evenly mixed with other raw materials of the concrete, and the obtained environmentally friendly steel slag concrete has good durability.

[0022] In summary, this application has at least the following beneficial effects: 1. The use of carboxyl glycoside derivatives can react with excess alkaline substances and inhibit the alkali-aggregate reaction during the concrete curing process; the anions obtained after the reaction of the carboxyl glycoside derivatives have carboxylate groups and multiple hydroxyl groups, which can chelate heavy metal ions on the one hand, and on the other hand, can destroy the double electric layer structure on the surface of steel slag powder particles and cement particles in the mixed concrete, improve the fluidity of the concrete, change the bonding mode of steel slag powder particles and cement particles, reduce microcracks and pores inside the concrete, and make the concrete particles more tightly bonded, preventing moisture and other harmful media from penetrating into the concrete, thereby improving the strength and durability of the concrete, and obtaining a highly durable environmentally friendly steel slag concrete; 2. Modify the steel slag powder. After soaking in soluble inorganic sulfate, some alkaline substances in the steel slag are dissolved, thereby reducing the alkali content in the steel slag powder. On the other hand, some heavy metals in the steel slag are also dissolved during the soaking process and converted into insoluble or insoluble precipitates, reducing the amount of soluble heavy metals in the steel slag powder. The formed precipitates will compensate for the loss of substances in the steel slag after dissolution, improve the stability of the steel slag powder, and thus improve the durability and environmental friendliness of the environmentally friendly steel slag concrete. DETAILED DESCRIPTION

[0023] raw material: The steel slag was crushed to a particle size of 0.5-1 mm, and the composition test results were as follows: Element CaO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> MgO <![CDATA[P2O5]]> <![CDATA[Fe2O3]]> MnO Content / wt% 42.549 27.883 8.927 6.633 2.641 7.843 0.176 Element f-CaO* Fe PbO <![CDATA[Na2O]]> CuO <![CDATA[ZrO2]]> <![CDATA[Cr2O3]]> Content / wt% 0.3425 1.7986 0.003 0.137 0.021 0.07 0.017 f-CaO is free limestone, that is, calcium oxide that has not been completely reacted in steel slag.

[0024] The cement is PO42.5 cement with a specific surface area of ​​352m 2 / kg.

[0025] The aggregate is limestone aggregate, and the particle size distribution range is 5 to 25 mm, and the specific particle size distribution mass ratio is 5-10 mm: 10-16 mm: 16-25 mm = 6:8:5.

[0026] The sand is ordinary river sand with a fineness modulus of 2.6 and a maximum particle size of 5 mm.

[0027] Sodium sulfate, aluminum sulfate, magnesium lignin sulfonate, isopentanol polyoxyethylene ether, magnesium phosphate, glucuronic acid, and galacturonic acid are all commercially available industrial grade products.

[0028] Preparation Example 1 A modified steel slag powder, the preparation method of which is as follows: Steel slag particles with a particle size of 0.5 to 1 mm were selected and immersed in a modified solution for 4.5 h. The modified solution was a composite solution of sodium sulfate and aluminum sulfate. The concentration of sodium sulfate was 1 mol / L and the concentration of aluminum sulfate was 0.06 mol / L.

[0029] After soaking, the samples were collected and dried, and then ground to a specific surface area of ​​490 ± 5 m 2 / kg, and modified steel slag powder was obtained.

[0030] Preparation Example 2 A modified steel slag powder, which is different from Preparation Example 1 in that the concentration of aluminum sulfate in the modified solution is 0.02 mol / L.

[0031] Preparation Example 3 A modified steel slag powder, which is different from Preparation Example 1 in that the concentration of aluminum sulfate in the modified solution is 0.04 mol / L.

[0032] Preparation Example 4 A modified steel slag powder, which is different from Preparation Example 1 in that the concentration of aluminum sulfate in the modified solution is 0.07 mol / L.

[0033] Preparation Example 5 A modified steel slag powder, which is different from Preparation Example 1 in that the concentration of aluminum sulfate in the modified solution is 0.1 mol / L.

[0034] Preparation Example 6 A modified steel slag powder is different from Preparation Example 1 in that the modification liquid is a sodium sulfate solution, and the concentration of the sodium sulfate solution is 1.06 mol / L.

[0035] Preparation Example 7 A steel slag powder, the preparation method of which is as follows: Select steel slag particles with a particle size of 0.5 to 1 mm and grind them to a specific surface area of ​​490 ± 5 m 2 / kg, and obtain steel slag powder.

[0036] Example 1 A highly durable environmentally friendly steel slag concrete, the raw materials of which include steel slag powder, cement, aggregate, sand, water reducing agent, glycoside derivative with carboxyl group and magnesium phosphate.

[0037] The steel slag powder is the modified steel slag powder prepared in Preparation Example 1.

[0038] The water reducing agent is magnesium lignin sulfonate.

[0039] The glycoside derivative with a carboxyl group is glucuronic acid.

[0040] The preparation method of highly durable environmentally friendly steel slag concrete is as follows: 280 kg of water, 2.0 kg of water reducing agent, and 2.7 kg of glycoside derivative with a carboxyl group are mixed evenly to obtain 284.7 kg of preparation water; 82 kg of steel slag powder, 316 kg of cement, 281 kg of aggregate, 117 kg of sand, 1.7 kg of magnesium phosphate and 284.7 kg of preparation water are mixed evenly to obtain highly durable environmentally friendly steel slag concrete.

[0041] The highly durable environmentally friendly steel slag concrete is poured or poured into the mold, and the required concrete components can be formed after solidification and curing.

[0042] Example 2 A highly durable environmentally friendly steel slag concrete, which is different from Example 1 in that the glycoside derivative with a carboxyl group is galacturonic acid.

[0043] Example 3 A highly durable environmentally friendly steel slag concrete, which is different from Example 1 in that the steel slag powder is the steel slag powder prepared in Preparation Example 7.

[0044] Example 4 A highly durable environmentally friendly steel slag concrete, which is different from Example 1 in that the steel slag powder is the modified steel slag powder prepared in Preparation Example 2.

[0045] Example 5 A highly durable environmentally friendly steel slag concrete, which is different from Example 1 in that the steel slag powder is the modified steel slag powder prepared in Preparation Example 3.

[0046] Example 6 A highly durable environmentally friendly steel slag concrete, which is different from Example 1 in that the steel slag powder is the modified steel slag powder prepared in Preparation Example 4.

[0047] Example 7 A highly durable environmentally friendly steel slag concrete, which is different from Example 1 in that the steel slag powder is the modified steel slag powder prepared in Preparation Example 5.

[0048] Example 8 A highly durable environmentally friendly steel slag concrete, which is different from Example 1 in that the steel slag powder is the modified steel slag powder prepared in Preparation Example 7.

[0049] Example 9 A highly durable environmentally friendly steel slag concrete, which is different from Example 1 in that the amount of magnesium phosphate used is 0, that is, no magnesium phosphate is added.

[0050] Example 10 A highly durable environmentally friendly steel slag concrete, which is different from Example 1 in that the water reducing agent is prenol polyoxyethylene ether.

[0051] Embodiment 11 A highly durable environmentally friendly steel slag concrete, which differs from Example 1 in that the amounts of raw materials used are different, specifically as follows: 262 kg of water, 1.3 kg of water reducer, 2.4 kg of carboxyl glycoside derivatives, 70 kg of steel slag powder, 300 kg of cement, 287 kg of aggregate, 112 kg of sand, and 1.3 kg of magnesium phosphate.

[0052] The preparation method is as follows: 262 kg of water, 1.3 kg of water reducing agent, and 2.4 kg of glycoside derivative with a carboxyl group are mixed evenly to obtain 265.7 kg of preparation water; 70 kg of steel slag powder, 300 kg of cement, 287 kg of aggregate, 112 kg of sand, 1.3 kg of magnesium phosphate and 265.7 kg of preparation water are mixed evenly to obtain highly durable environmentally friendly steel slag concrete.

[0053] Example 12 A highly durable environmentally friendly steel slag concrete, which differs from Example 1 in that the amounts of raw materials used are different, specifically as follows: 286 kg of water, 2.2 kg of water reducing agent, 3.1 kg of carboxyl glycoside derivatives, 86 kg of steel slag powder, 320 kg of cement, 296 kg of aggregate, 120 kg of sand, and 1.9 kg of magnesium phosphate.

[0054] The preparation method is as follows: 286 kg of water, 2.2 kg of water reducing agent, and 3.1 kg of glycoside derivative with a carboxyl group are mixed evenly to obtain 265.7 kg of preparation water; 86 kg of steel slag powder, 320 kg of cement, 296 kg of aggregate, 120 kg of sand, 1.9 kg of magnesium phosphate and 291.3 kg of preparation water are mixed evenly to obtain highly durable environmentally friendly steel slag concrete.

[0055] Comparative Example 1 The invention discloses steel slag concrete, whose raw materials include steel slag powder, cement, aggregate, sand, water reducing agent and magnesium phosphate.

[0056] The steel slag powder is the modified steel slag powder prepared in Preparation Example 1.

[0057] The water reducing agent is magnesium lignin sulfonate.

[0058] The preparation method of steel slag concrete is as follows: Mix 280 kg of water and 2.0 kg of water reducing agent to obtain 282 kg of preparation water; 82 kg of steel slag powder, 316 kg of cement, 281 kg of aggregate, 117 kg of sand, 1.7 kg of magnesium phosphate and 282 kg of preparation water were uniformly mixed to obtain steel slag concrete.

[0059] The concrete obtained in Examples 1 to 13 and Comparative Example 1 was subjected to compressive strength test, chloride ion permeability resistance test, carbonization test and heavy metal ion seepage test.

[0060] Compressive strength test: According to GB / T 50081-2019, the compressive strength of 28 days is tested and the result is expressed as compressive strength.

[0061] Resistance to chloride ion penetration: The test is carried out in accordance with GB / T 50082-2024. The results are expressed as chloride ion permeability coefficient. The smaller the chloride ion permeability coefficient, the better the concrete's resistance to chloride ion permeability and the better its durability.

[0062] Heavy metal leaching test: According to GB / T30810-2014, after removing the aggregate, the mortar sample is prepared with the same raw materials and tested. The results are expressed as the ion concentration of Mn, Pb, Cr, and Cu in the leaching solution. The lower the concentration, the better the environmental protection of the concrete.

[0063] Table 1. Test results of Examples 1 to 12 and Comparative Example 1 Combined with Table 1, by comparing Examples 1 to 2 and Comparative Example 1, it can be seen that carboxyl-containing glycoside derivatives are added to the raw materials of the environmentally friendly steel slag concrete of Examples 1 to 2, and carboxyl-containing glycoside derivatives are not added to the raw materials of the steel slag concrete of Comparative Example 1. In the test results, the compressive strength of the environmentally friendly steel slag concrete of Examples 1 to 2 is better than that of Comparative Example 1, and the chloride ion permeability coefficient of the environmentally friendly steel slag concrete of Examples 1 to 2 is significantly lower than that of Comparative Example 1. In the heavy metal leaching test of the environmentally friendly steel slag concrete of Examples 1 to 2, the ion concentrations of Mn, Pb, Cr, and Cu are significantly lower than those of Comparative Example 1. Therefore, the environmentally friendly steel slag concrete of Examples 1 to 2 is better than that of Comparative Example 1 in strength, durability, and environmental protection, especially in durability and environmental protection. Significant improvement.

[0064] This is because the carboxyl glycoside derivatives in Examples 1 and 2 can react with excess alkaline substances to inhibit the alkali-aggregate reaction during the concrete curing process; the anions obtained after the reaction of the carboxyl glycoside derivatives have carboxylate and multiple hydroxyl groups, which can chelate heavy metal ions on the one hand, and on the other hand, can also destroy the double electric layer structure on the surface of steel slag powder particles and cement particles in the mixed concrete, improve the fluidity of the concrete, change the bonding mode of the steel slag powder particles and cement particles, reduce the microcracks and pores inside the concrete, and make the concrete particles more tightly bonded, prevent moisture and other harmful media from penetrating into the concrete, thereby improving the strength and durability of the concrete, so as to obtain a highly durable environmentally friendly steel slag concrete.

[0065] Further comparison between Example 1 and Example 2 shows that the environmentally friendly steel slag concrete of Example 1 is superior to that of Example 2 in terms of strength, durability and environmental friendliness. Therefore, glucuronic acid is preferably used as the glycoside derivative with a carboxyl group in the present application.

[0066] Combining Example 1, Example 3 and Example 8, it can be seen that the steel slag powder used in Example 3 is unmodified steel slag powder, Example 8 uses modified steel slag powder treated by immersion in sodium sulfate solution, and Example 1 uses steel slag powder treated by immersion in a composite solution of sodium sulfate and aluminum sulfate.

[0067] In this regard, the steel slag particles are soaked in a soluble inorganic sulfate, and some alkaline substances in the steel slag are dissolved, thereby reducing the alkali content in the steel slag powder. On the other hand, during the soaking process, some heavy metals in the steel slag are also dissolved and converted into insoluble or insoluble precipitates, reducing the amount of soluble heavy metals in the steel slag powder. In addition, the formed precipitates will compensate for the loss of substances in the steel slag after dissolution, thereby improving the stability of the steel slag powder and thereby improving the durability and environmental friendliness of the environmentally friendly steel slag concrete.

[0068] When a solution composed of sodium sulfate and aluminum sulfate is selected, due to the difficulty of ion diffusion during the immersion treatment of steel slag particles, the concentration of alkaline substances in the micropores of the steel slag particles is the highest, followed by the surface, and the concentration is the lowest in the surrounding solution. The aluminum ions dissolved by aluminum sulfate are dispersed in the aqueous phase and penetrate into the micropores of the steel slag, and the alkaline substances in the steel slag are accelerated to dissolve through reaction with hydroxide. It can also improve the stability of the steel slag powder, thereby improving the durability and environmental friendliness of the environmentally friendly steel slag concrete.

[0069] Therefore, in the test results: the compressive strength of Example 1 is greater than that of Example 8, and the compressive strength of Example 8 is greater than that of Example 3; the chloride ion permeability coefficient of Example 1 is less than that of Example 8, and the chloride ion permeability coefficient of Example 8 is less than that of Example 3; the ion concentrations of Mn, Pb, Cr, and Cu in the heavy metal leaching test of Example 1 are less than those of Example 8, and the ion concentrations of Mn, Pb, Cr, and Cu in the heavy metal leaching test of Example 8 are less than those of Example 3; therefore, the environmentally friendly steel slag concrete of Example 1 is superior to that of Example 8 in strength, durability, and environmental protection, and the environmentally friendly steel slag concrete of Example 8 is superior to that of Example 3 in strength, durability, and environmental protection.

[0070] In combination with Example 1 and Examples 4 to 7, both Example 1 and Examples 4 to 7 use steel slag powder treated by immersion in a composite solution of sodium sulfate and aluminum sulfate. The difference is that the molar ratio of aluminum sulfate to sodium sulfate during the immersion treatment is different. Combined with the test results, the compressive strength is from large to small in Example 1, Example 6, Example 7, Example 5, and Example 4, and the chloride ion permeability coefficient is from small to large in Example 1, Example 6, Example 5, Example 7, and Example 4. The ion concentrations of Mn, Pb, Cr, and Cu in the heavy metal leaching test are from small to large in Example 1, Example 6, Example 5, Example 7, and Example 4. Therefore, in the present application, the molar ratio of sodium sulfate to aluminum sulfate during the immersion treatment in the steel slag modification process is preferably 100:4 to 10.

[0071] Comparing Example 1 and Example 9, it can be seen that the compressive strength of the environmentally friendly steel slag concrete of Example 1 in the test results is better than that of Example 9, the chloride ion permeability coefficient of the environmentally friendly steel slag concrete of Example 1 is lower than that of Example 9, and the ion concentrations of Mn, Pb, Cr, and Cu in the heavy metal leaching test of the environmentally friendly steel slag concrete of Example 1 are lower than those of Example 9. The environmentally friendly steel slag concrete of Example 1 is better than that of Example 9 in strength, durability, and environmental protection. Therefore, the addition of magnesium phosphate to the raw materials of environmentally friendly steel slag concrete in this application can not only improve the early strength of concrete, solidify heavy metal ions, and improve the microstructure and density of concrete, thereby improving its overall durability. In addition, magnesium phosphate cement also has good resistance to sulfate erosion, which helps to extend the service life of concrete.

[0072] By comparing Example 1 and Example 10, it can be seen that the ion concentrations of Mn, Pb, Cr, and Cu in the heavy metal leaching test of the environmentally friendly steel slag concrete in Example 1 are lower than those in Example 10, and the environmentally friendly steel slag concrete in Example 1 is better than that in Example 10 in terms of environmental protection. Therefore, using magnesium lignin sulfonate as a water reducer can not only reduce the water consumption of concrete, but also further solidify heavy metal ions, thereby long-term reducing the possibility of heavy metal ions migrating from concrete to the environment, thereby improving the environmental protection of steel slag concrete.

[0073] In addition, in combination with Example 1 and Examples 11-12, the compressive strength of Examples 11-12 is similar to that of Example 1, the chloride ion permeability coefficient of the environmentally friendly steel slag concrete of Examples 11-12 is similar to that of Example 1, and the ion concentrations of Mn, Pb, Cr, and Cu in the heavy metal leaching test of the environmentally friendly steel slag concrete of Examples 11-12 are similar to that of Example 1. Therefore, the environmentally friendly steel slag concrete of Examples 11-12 also has excellent strength, durability, and environmental protection.

[0074] This specific embodiment is only an explanation of the present invention, and it is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to this embodiment as needed, but as long as it is within the scope of protection required by the present invention, it will be protected by the patent law.

Claims

1. A highly durable environmentally friendly steel slag concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 70~86 parts of steel slag powder, 300~320 parts of cement, Aggregate 287~296 parts, Sand 112~120 parts, Water reducing agent 1.3~2.2 parts, 2.4~3.1 parts of glycoside derivative with carboxyl group.

2. The highly durable environmentally friendly steel slag concrete according to claim 1, characterized in that: The glycoside derivative with a carboxyl group is glucuronic acid.

3. The highly durable environmentally friendly steel slag concrete according to claim 1, characterized in that: The steel slag powder is a modified steel slag powder, which is obtained by grinding steel slag particles after soaking them in soluble inorganic sulfate.

4. The highly durable environmentally friendly steel slag concrete according to claim 3, characterized in that: The soluble inorganic sulfate is obtained by compounding sodium sulfate and aluminum sulfate.

5. The highly durable environmentally friendly steel slag concrete according to claim 4, characterized in that: The molar ratio of the sodium sulfate to the aluminum sulfate is 100:4-10.

6. The highly durable environmentally friendly steel slag concrete according to claim 1, characterized in that: It also includes 1.3 to 1.9 parts of magnesium phosphate.

7. The highly durable environmentally friendly steel slag concrete according to claim 6, characterized in that: The water reducing agent is magnesium lignin sulfonate.

8. The method for preparing a highly durable environmentally friendly steel slag concrete according to claims 1 to 7, characterized in that: The following steps are involved: Mix water, water reducing agent and glycoside derivative with carboxyl group to obtain preparation water. The remaining raw materials such as steel slag powder, cement, aggregate, sand and the preparation water are evenly mixed to obtain highly durable environmentally friendly steel slag concrete.